Earnings management in Malaysia: the case of cash from operations and the behaviour of discretionary accruals / Rosnia Masruki - Masruki, Rosnia (2004)
The objectives of this study are to investigate the relationship between the operating performances of firms listed on the Main Board of the Bursa Malaysia and to examine the behaviour of discretionary accruals during the period of 1999-2002. This dissertation hypothesized that the degree of earnings management will depend on the level of the firm operating performances. Initially, the sample firms are divided into 10 portfolios based on relative cash from operations (CFO) rankings to test if there are systematic differences in discretionary accruals across portfolios. Four test methods (a mean accrual test, a correlation test, a regression analysis and a sign-change ratio test) are used to study if operating performances affect discretionary accruals differently. To further test the earning management hypotheses, two accrual estimation approaches (discretionary accruals and total accruals) are employed. The empirical evidence supports the predictions. It suggests that firms from various industries manage earnings, when operating performance is poor. The firms tend to choose income-increasing strategies, specifically, when the operating performance is extremely poor. In fact, some firms tend to take a big bath whereas some of the exceptionally well performing firms tend to select income-decreasing strategies.